The relationship between interpersonal trust and aloneliness among college students: an analysis of the mediating effect of pain self-representation - Lin, Yan (Pacific International Journal, 2024)
This study aimed to elucidate the relationship between interpersonal trust and aloneliness by constructing a mediating model. The model sought to clarify the role of painful self-disclosure as a mediator between interpersonal trust and aloneliness. A questionnaire was used to evaluate the levels of interpersonal trust, painful self-disclosure, and aloneliness among 649 college students. The findings indicated that there was a negative correlation between painful self-disclosure and aloneliness. Additionally, there was a negative correlation between interpersonal trust and painful self-disclosure. A strong positive link existed between interpersonal trust and aloneliness. (2) Painful self-disclosure acts as a partial mediator in the connection between interpersonal trust and aloneliness among college students. This means that interpersonal trust not only has a direct impact on the aloneliness of college students, but also indirectly affects aloneliness through the process of painful self-disclosure. The findings not only alleviate the alone experienced by college students, but also have the potential to enhance the precision of mental health teaching.